The Influence E-Service Quality On E-Repurchase Intention Through E-Trust As Mediation Variable (Study on RedDoorz Mobile Apps Users in Bogor City) - Ame Angelique Br. Sembiring Depari; Reni Shinta Dewi; Naili Farida (Jurnal Ilmu Administrasi Bisnis, 2024)
Abstract: The emergence of online hotel booking in Indonesia has led to intense competition in the hospitaly and tourism industry. As a result, companies need to strengthen the quality of their electronic services to build user trust and enchance the likelihood of repeat purchases. This study aims to determine the effect of E-Service Quality on RedDoorz Mobile Apps’s E-Repurchase Intention Through E-Trust as an Mediation Variable. This type of research is explanatory research with a quantitative approach. Data collection techniques were carried out through questionnaries distributed to 100 respondents with a nonprobability sampling technique, namely purposive sampling and processed using SmartPLS 3.3.3. The results show that e-service quality has a positive on e-repuchase intention, e-service quality has a positive on e-trust, e-trust has a positive on e-repurchase intention, e-service quality has a positive indirect effect through e-trust on e-repurchase intention. This study is cross-sectional, meaning that it can only analyze the characteristics of respondents within a specific period.. A suggestion in this research is for the customer service in the RedDoorz mobile apps to be more responsive in processing refund requests. Additionally, the company should follow up on hotels that do not display room photos accurately according to their actual conditions.Keywords: e-service quality; e-trust; e-repurchase intentionAbstraksi: Munculnya berbagai aplikasi booking hotel online di Indonesia menyebabkan persaingan ketat dalam bisnis perhotelan dan pariwisata, sehingga perusahaan perlu memperkuat kualitas pelayanan elektronik yang dapat meningkatkan kepercayaan pengguna serta dapat meningkatkan niat seseorang untuk melakukan pembelian ulang. Penelitian ini memiliki tujuan untuk mengetahui Pengaruh E-Service Quality terhadap E-Repurchase Mobile Apps RedDoorz melalui E-Trust sebagai Variabel Mediasi. Tipe penelitian ini adalah explanatory research dengan pendekatan kuantitatif. Teknik pengumpulan data dilakukan menggunakan kuesioner yang dibagikan kepada 100 responden dengan teknik pengambilan sampel nonprobability sampling yaitu purposive sampling dan diolah menggunakan aplikasi SmartPLS 3.3.3. Hasilnya adalah menurut pandangan Parasuraman (2005) bahwa e-service quality berpengaruh positif terhadap e-repurchase intention, e-service quality berpengaruh positif terhadap e-trust, e-trust berpengaruh positif terhadap e-repurchase intention, e-service quality berpengaruh positif dalam indirect effect melalui dan e-trust terhadap e-repurchase intention. Penelitian ini bersifat cross-sectional, yaitu penelitian ini hanya dapat menganalisis karakteristik responden dalam suatu periode tertentu. Saran dalam penelitian ini adalah agar customer service pada mobile apps RedDoorz lebih tanggap dalam memproses permohonan pengembalian dana. Selain itu, perusahaan harus melakukan tindak lanjut terhadap hotel yang tidak menampilkan foto kamar sesuai dengan kondisi aslinya.Kata kunci: e-service quality; e-trust; e-repurchase intention